The many hands of the state theorizing political authority and social control - Morgan, Kimberly J. 1970-; Orloff, Ann Shola 1953- (Cambridge University Press, 2017)
The state is central to social scientific and historical inquiry today, reflecting its importance in domestic and international affairs. States kill, coerce, fight, torture, and incarcerate, yet they also nurture, protect, educate, redistribute, and invest. It is precisely because of the complexity and wide-ranging impacts of states that research on them has proliferated and diversified. Yet, too many scholars inhabit separate academic silos, and theorizing of states has become dispersed and disjointed. This book aims to bridge some of the many gaps between scholarly endeavors, bringing together scholars from a diverse array of disciplines and perspectives who study states and empires. The book offers not only a sample of cutting-edge research that can serve as models and directions for future work, but an original conceptualization and theorization of states, their origins and evolution, and their effects